Digital Entrepreneurship Competency Training for Students of SMA Negeri 2 Binjai - Ruly Dwi Arista; Bambang Suwarno (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
High school students as the nation's future young generation, there needs to be an increase in competence towards the development of digital technology today. Digital technology has become their consumption and can be used to earn a living. However, its use has not been maximized so that it can be used to overcome the nation's current problems, namely the large number of unemployed and the difficulty of getting a job. Digital entrepreneurship training seeks to create a creative and active mental attitude and spirit to try to increase income in every business activity. This community service activity will use the classroom action research method. In this method, students of SMA Negeri 2 Binjai as training participants and UNPAB lecturers will act as speakers and assessors. The method used is the Progressive Differentiation and Integrative Reconciliation Method, which is a method to improve students' understanding as seen from the increase in learning outcomes scores. Also, as a Classroom Action Research Method that will show the results of students' understanding of the use of digital social media as a suggestion to develop and arouse students' entrepreneurial spirit, it is hoped that there will be quality learning that can be applied when working in the business and industrial world. The results of activities in the community at SMA 2 Binjai can be seen from the results of the principle of Progressive Differentiation and Integrative Reconciliation, there is an increase in the score for understanding the use of digital entrepreneurship on Facebook, Instagram and Twitter from an average pre-test score of 48.33% to a post-test result of 92.71 % which is obtained.